Distribution frequency of Post Odontectomy Complications under General Anesthesia in Universitas Padjadjaran Dental and Oral Hospital (RSGM Unpad) Bandung - Khaq, Arina Al; Sjamsudin, Endang; Yuza, Abel Tasman (Padjadjaran Journal of Dentistry, 2022)
ABSTRACTIntroduction: Odontectomy is a surgical procedure to remove an impacted tooth. Some cases of odontectomy are performed under general anesthesia because it has risks and complications that need to be considered, such as a patient with mental or physical disorder, difficulty level of the impacted tooth, number of impacted teeth extracted, and operative duration. This study aimed to determine the distribution frequency of post-odontectomy complications under general anesthesia in Universitas Padjadjaran Dental and Oral Hospital (RSGM Unpad), Bandung. Methods: This study was a cross-sectional descriptive study using retrospective data of medical records of a patient who underwent odontectomy under general anesthesia from 2017 until 2018 in RSGM Unpad. Samples were taken using a purposive non-probability sampling technique by setting inclusion criteria such as undamaged medical records and providing patient data on the first and a week control visit. The variables, including age, gender, classification of impacted teeth, number of teeth, and complications, were assessed in this study. The minimum sample size was determined by using the Slovin formula. The minimum sample required is 94%- 95% confidence level and 5% margin of error. Results: The data that had been collected shows that the number of female patients (67%), male patients (37%), the most common age was 21-30 years (52%), and odontectomy in 4 third molars (73%). Odontectomy that performed on four third molars (73%) with the ordinary post odontectocmy complications found in the female patient, such as trismus (2%), prolonged pain (7%), edema (3%), paraesthesia (3%). Conclusion: Distribution frequency of post-odontectomy complications under general anesthesia in RSGM Universitas Padjadjaran Banding is relatively low.Keywords: frequency; odontectomy; general anesthesia; complications; impacted tooth